2017
DOI: 10.1128/aac.02458-16
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Characterization of Two KPC-Producing Klebsiella Isolates Collected in 1997 in New York City

Abstract: Klebsiella pneumoniae carbapenemase (KPC)-producing Enterobacteriaceae have now become a global public health threat. However, the origin of this pandemic and the characterization of pre-2003 bla KPC -harboring plasmids remain unknown. Here we used next-generation sequencing to characterize two KPC-2-producing K. pneumoniae and K. michiganensis isolates collected from a New York City hospital in 1997. Although identified in two different Klebsiella species, the bla KPC-2 gene was harbored by Tn4401b transposon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 33 publications
3
19
0
Order By: Relevance
“…In this study, the lowest resistance was attributed to carbapenems based on the antibiotic susceptibility tests; this finding is consistent with the results of a study by Bina et al, which indicated the highest resistance to carbapenem (Bina et al, 2015). Considering the increasing spread of antimicrobial resistance (AMR) in hospital settings, the findings of the present study are similar to those reported by (Eilertson et al, 2017), and (Kontopoulou et al, 2010). These findings warrant more attention by the intensive care unit personnel to limit the potential risk of AMR in hospitals.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, the lowest resistance was attributed to carbapenems based on the antibiotic susceptibility tests; this finding is consistent with the results of a study by Bina et al, which indicated the highest resistance to carbapenem (Bina et al, 2015). Considering the increasing spread of antimicrobial resistance (AMR) in hospital settings, the findings of the present study are similar to those reported by (Eilertson et al, 2017), and (Kontopoulou et al, 2010). These findings warrant more attention by the intensive care unit personnel to limit the potential risk of AMR in hospitals.…”
Section: Discussionsupporting
confidence: 88%
“…Other plasmid replicon groups, such as IncN, IncP, IncX, IncU, IncI, A/C, IncR, and L/M, are also occasionally reported in KPC‐producing K. pneumoniae . Moreover, these plasmid replicon groups are also associated with K. pneumoniae strains producing other carbapenemases.…”
Section: Plasmid Biology and Incompatibility Groupsmentioning
confidence: 99%
“…However, in the last decade, KPC has also been reported in other species of Enterobacteriaceae , including Escherichia coli , Enterobacter spp., Klebsiella oxytoca , Proteus mirabilis , Serratia marcescens , Morganella morganii , and Citrobacter freundii , among others . KPC carbapenemases are widely distributed worldwide, but they are mostly reported in the United States, where they cause majority of reported cases of infection . In the United States, KPC producers are usually associated with hospital outbreaks caused by patient‐to‐patient transmission of clonally related resistant organisms .…”
Section: Classification Of Carbapenemasesmentioning
confidence: 99%
See 2 more Smart Citations